How a Traditional Homemaker Predicts: An Ethnographic Study - Vici Suciawati; Mohamad Gilar Jatisunda; Nia Kania (Malikussaleh Journal of Mathematics Learning (MJML), 2021)
Intuition is the first way humans get knowledge. A worker in making a traditional West Java house works using his experience to be able to determine how many building materials are needed to become a house. The roof of the house is one part that is quite complicated to determine the amount of wood needed. Workers using intuition based on experience that has been experienced greatly determine the accuracy of the measure. Through this research, the researcher hopes that the method of determining the amount of wood used to make the roof (suhunan) of houses in West Java has added scientific value because it is related to existing mathematical concepts. The subjects of this study were workers who made traditional houses in West Java Regency. This study uses a qualitative method with an ethnographic approach. This study aims to describe an in-depth study of how to determine the amount of wood used to make traditional houses and its relation to mathematical concepts. The results showed that the workers who made the traditional houses started outing for the first time by calculating the number of wood chips needed to make the KAP intact to make the roof from it, they were easier to determine the amount of wood needed.